Influences Of Macroeconomic Variables On The Malaysian Stock Market - Mei, Cheng Mei (2005)
This study examines the determinants of stock returns in the Malaysian stock market for the period from January 1992 to December 2003 by investigating the influences of eight macroeconomic variables, viz. inflation rates, industrial production, Kuala Lumpur Stock Exchange Composite Index (KLCI), Dow Jones Industrial Average, Nikkei Industrial Average, money supply, interest rates and exchange rates.